SOA based fiber ring laser with Fiber Bragg Grating - Ahmad, Harith; Ooi, H.C.; Sulaiman, Abdul Hadi; Thambiratnam, Kavintheran; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (John Wiley & Sons, 2008)
A semiconductor optical amplifier fiber ring laser (SOAFRL) utilizing a Fiber Bragg Grating (FBG) is demonstrated. The laser operates at a wavelength of 1547.64 nm, equal to the Bragg wave-length. By removing FBG, the SOAFRL shows a multi-modes output due to the resonant characteristics of the semiconductor optical amplifiers (SOA's) gain. The output power ripple is observed around 5 dB. The experimental results show that when the saturation level is reached, the SOAFRL with the FBG shows a higher saturation current and peak power compared to that of the SOAFRL without the FBG. Mode competition in the cavity for the free-running ring SOAFRL results in a lower peak power as well as a broader bandwidth as the current is increased. By incorporating the FBG in the SOAFRL, a losing wavelength is generated and as such the side mode suppression ratio (SMSR) of the laser is significantly improved, resulting in a higher peak power at higher bias currents.